(untitled) (Indian Journal of Arid Horticulture, 2025)
Micro propagation in guava is impaired by the problem of oxidative browning of explants and culture media during culture establishment phase. The study was conducted to see the efficiency of different techniques and antioxidant compounds on controlling phenolic browning and ultimate culture establishment for micropropagation. Significant differences were recorded between Allahabad Safeda and Aneuploid No. 82 in respect to quantum of exudated phenol and per cent sprouting. Agitation of explants in 0.5% PYPP and 2% sucrose for 40 minutes followed by a quick dip in a solution of citric acid and ascorbic acid @75 mg L and 50 mg L respectively before inoculation resulted in maximum sprouting and reduced exudation of phenol in both the genotypes. Mean phenol exudation in different seasons from nodal and shoot tip explant indicated lower phenol exudation and higher sprouting in Allahabad Safeda as compared to Aneuploid No. 82. Significantly higher sprouting was recorded when the explants were collected during spring or summer as compared to that of autumn season. The quantum of phenol leached into the medium and percent sprouting was found to be negatively correlated